Reviewing outcomes of psychological interventions with torture survivors: Conceptual, methodological and ethical Issues - Patel, Nimisha; Williams, Amanda C de C; Kellezi, Blerina (Torture Journal, 2018)
Background: Torture survivors face multiple problems, including psychological difficulties, whether they are refugees or remain in the country where they were tortured. Provision of rehabilitation varies not only with the needs of survivors and resources available but also with service models, service provider preferences and the local and country context. Despite increasing efforts in research on the effectiveness of psychological interventions with torture survivors, results are inconclusive. Methods: We undertook a Cochrane systematic review of psychological, social and welfare provision, with meta-analysis to best estimate efficacy. The process raised conceptual, methodological and ethical issues of relevance to the wider field. Findings: We searched very widely, but rejected hundreds of papers which recommended treatment without providing evidence. We found nine randomized controlled trials, from developed and under-resourced settings. All conceptualized survivors’ problems in psychiatric terms, using outcomes of post-traumatic stress symptoms, distress, and quality of life, by self-report, with or without translation or unstandardized interpretation, and with little mention of cultural or language issues. None used social or welfare interventions. Four related studies used narrative exposure therapy (NET) in a brief form, and without ensuring a safe setting as recommended. Five used mixed methods, including exposure, cognitive behavioral therapy, and eye movement desensitization. Combined, the studies showed no immediate improvement in PTSD, distress, or quality of life; at six months follow-up, a minority showed some improvement in PTSD and distress, although participants remained severely affected. Conclusions: While applauding researchers’ commitment in running these trials, we raise ethical issues about exposure in particular, and about the effects of shortcomings in methodology, particularly around assessment using unfamiliar cultural frameworks and language, and the lack of concern about dropout which may indicate harm. The issues addressed aid interpretation of existing research, and guide clinical practice as well as future studies evaluating its effectiveness.